Komunikasi Politik Kedutaan Besar Republik Indonesia (KBRI) Kuala Lumpur Dalam Promosi Budaya Indonesia Di Malaysia - Amir; Nur Alim; Yusmanizar (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2023)
The increasing cases of Indonesian cultural claims by Malaysia make the government through the Indonesian Embassy in Kuala Lumpur will increase efforts to promote Indonesian culture in Malaysia through various political communication strategies. The promotion of Indonesian culture is carried out to introduce the richness of Indonesian culture to the Malaysian people, and to increase understanding and tolerance between the two countries in terms of culture as well as the process towards cultural registration to UNESCO Intangible Cultural Heritage. This study aims to analyze the form of Political Communication of the Embassy of the Republic of Indonesia (KBRI) Kuala Lumpur in the Promotion of Indonesian Culture in Malaysia, and identify the Political Communication of the Embassy of the Republic of Indonesia Kuala Lumpur can improve the Promotion of Indonesian Culture in Malaysia. The results showed that in conducting cultural promotion, political communication can help the Indonesian Embassy in Kuala Lumpur in influencing the perceptions and views of the Malaysian people towards Indonesian culture. The form of political communication of the Indonesian Embassy in Malaysia is by meeting with the Malaysian government directly, organizing cultural festivals, using Malaysian media as publications and promotions using social media. With the help of various elements such as the Indonesian people, government agencies and the Malaysian government itself can increase the promotion of Indonesian culture in Malaysia